Keefektifan Pelatihan Teknik Parafrase dan Teknik Sitasi Menggunakan Mendeley Bagi Mahasiswa PGSD untuk Menghindari Plagiasi - Dyah Indraswati; Arif Widodo (Journal on Education, 2023)
This study aims to determine the effectiveness of training in paraphrasing and citation techniques using Mendeley paraphrasing and citation skills for PGSD students, Mataram University. Type of this research is a quantitative research using a pre-experimental design method type one group pretest-posttest. This research is included in the population study because all participants are the research subjects. The instruments used were 10 multiple choice questions and 5 short questions which were used as pretest and posttest questions. The data analysis technique used a normality test as a prerequisite for analysis, paired sample t-test, an effect size test, and an N-Gain test. All data are normally distributed as indicated by the normality test. The paired sample t-test test shows a difference between the pretest and posttest values ​​where the posttest value is higher than the pretest value. Test effect size d = -1.90521 is in the small category because <0.05. This means that training in paraphrasing and citation techniques using Mendeley has little effect on students' ability to paraphrase and cite. N-Gain test with SPSS 18.0, the average N-Gain score was 54.9271 or 55% or included in the less effective category. The conclusion is that training in paraphrasing and citation techniques using Mendeley to avoid plagiarism is less effective in improving paraphrasing and citation skills for 7th-semester students of PGSD, University of Mataram.